Kedudukan Hukum Putusan DKPP terhadap Pelanggaran Kode Etik Anggota Bawaslu yang Merangkap sebagai Pengurus Partai Politik - Manik, Ewaldo Harian (CV. Era Digital Nusantara, 2025)
Elections are a manifestation of people's sovereignty in a democratic system that requires transparency, accountability, and integrity. This research analyzes the executory power of the Election Organizers’ Honorary Council (DKPP) decisions in handling violations of the code of ethics in election administration, particularly by members of the Election Supervisory Body (Bawaslu) who simultaneously hold positions in political parties. Using a normative juridical approach, which involves an analysis of regulations and DKPP decisions, this study identifies the effectiveness of decision implementation and the obstacles that hinder the execution process. The findings indicate that DKPP decisions are final and binding as stipulated in Law Number 7 of 2017 on General Elections (Law Number 7/ 2017). However, their implementation is often hindered by DKPP’s limited authority, which only allows it to issue sanction recommendations. Other challenges include lengthy administrative processes and lack of coordination with other institutions, such as the President or the House of Representatives (DPR). Case studies highlight DKPP’s crucial role in upholding integrity by sanctioning violators while also rehabilitating individuals who are not proven guilty. The study’s recommendations include strengthening the execution mechanisms of DKPP decisions through regulatory reforms, enhancing transparency through digital systems such as the Political Party Information System (Sipol), and reinforcing ethics education for election organizers. This research contributes to the development of constitutional law, particularly in ensuring justice and integrity in Indonesia’s democratic processes.